Family management and Industry 4.0: Different effects in different geographical areas? An analysis of the less developed regions in Italy - Marco Pini (Journal of Entrepreneurship, Management and Innovation)
This paper tests the impact of different types of management within family businesses on digital innovation related to Industry 4.0 investments, from a geographical perspective. The data set consists of 3,000 Italian manufacturing small- and medium–sized enterprises. Using probit models, the results show that while in the more advanced area (center-north) external management affects the propensity for innovation significantly, in the less developed area (Southern Italy) external management requires an additional and simultaneous investment in R&D to drive a firm’s innovation. This suggests that innovation policy should define incentives that also help enhance new management business models and take into account behavioral features of different firms in relation to the level of the development of the geographical areas in which they operate.